2017
DOI: 10.1371/journal.pone.0186962
|View full text |Cite
|
Sign up to set email alerts
|

Serosurveillance for pandemic influenza A (H1N1) 2009 virus infection in domestic elephants, Thailand

Abstract: The present study conducted serosurveillance for the presence of antibody to pandemic influenza A (H1N1) 2009 virus (H1N1pdm virus) in archival serum samples collected between 2009 and 2013 from 317 domestic elephants living in 19 provinces situated in various parts of Thailand.To obtain the most accurate data, hemagglutination-inhibition (HI) assay was employed as the screening test; and sera with HI antibody titers ≥20 were further confirmed by other methods, including cytopathic effect/hemagglutination base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Purified recombinant EEHV1A gB, gH/gL or gL (diluted in PBS; 100 µL/well) were coated overnight on Nunc MaxiSorp high protein-binding capacity ELISA plates (Thermo Fisher Scientific). Subsequently, plates were washed three times with PBST (PBS + 0.05% Tween-20) and incubated with blocking buffer (PBS containing 0.1% Tween 20 and 3% BSA [ w / v ] for 2 h. Next, plates were washed (three times with PBST) and 100 µL serum diluted in blocking buffer was added to the wells for 1 h. Plates were washed (three times with PBST), and incubated with 100 µL HRP-conjugated recombinant Protein A/G (0.5 µg/mL diluted in blocking buffer; Pierce), previously reported to bind elephant IgG [ 25 , 26 ], for 1 h. After washing (three times with PBST), 100 µL/well TMB Substrate (Surmodics, Eden Prairie, MN, USA) was added, plates were incubated for 10 min in the dark, and the reaction was stopped by adding 100 µL 12.5% H 2 SO 4 . Optical density (OD) was measured at 450 nm in an EL-808 ELISA reader (BioTEK, Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Purified recombinant EEHV1A gB, gH/gL or gL (diluted in PBS; 100 µL/well) were coated overnight on Nunc MaxiSorp high protein-binding capacity ELISA plates (Thermo Fisher Scientific). Subsequently, plates were washed three times with PBST (PBS + 0.05% Tween-20) and incubated with blocking buffer (PBS containing 0.1% Tween 20 and 3% BSA [ w / v ] for 2 h. Next, plates were washed (three times with PBST) and 100 µL serum diluted in blocking buffer was added to the wells for 1 h. Plates were washed (three times with PBST), and incubated with 100 µL HRP-conjugated recombinant Protein A/G (0.5 µg/mL diluted in blocking buffer; Pierce), previously reported to bind elephant IgG [ 25 , 26 ], for 1 h. After washing (three times with PBST), 100 µL/well TMB Substrate (Surmodics, Eden Prairie, MN, USA) was added, plates were incubated for 10 min in the dark, and the reaction was stopped by adding 100 µL 12.5% H 2 SO 4 . Optical density (OD) was measured at 450 nm in an EL-808 ELISA reader (BioTEK, Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the result indicated that human H1 virus infection was common in tiger cubs originally from Kanchanaburi province, western Thailand in 2011 and 2013. Our previous study demonstrated that the source of human H1 viral infection in Thai elephants likely came from mahouts or tourists who engaged in activities involving with elephants [19].…”
Section: Discussionmentioning
confidence: 99%
“…The positive samples obtained from the HI assay were further determined for neutralizing (NT) antibody using microNT assay. The protocol for microNT assay was followed by that previously described [13, 19]. Briefly, 60 µl of the treated serum was serially 2-fold diluted in EMEM (Gibco) in 96-well microculture plates in duplicate at an initial dilution of 1:20 and then added the tested virus at the final concentration of 100 TCID50/well.…”
Section: Methodsmentioning
confidence: 99%
“…Next, plates were washed (three times with PBST) and 100 µl serum diluted in blocking buffer was added to the wells for 1 hour. Plates were washed (three times with PBST), and incubated with 100 µl HRP-conjugated recombinant Protein A/G (0.5 µg/ml diluted in blocking buffer; Pierce), previously reported to bind elephant IgG (36, 37), for 1 hour. After washing (three times with PBST), 100 µl/well TMB Substrate (Surmodics) was added, plates were incubated for 10 minutes in the dark, and the reaction was stopped by adding 100 µl 12,5% H2SO4.…”
Section: Methodsmentioning
confidence: 99%
“…Sera with high background values (ODvalues >1 in the wells lacking antigen) were excluded from analysis (N=8, all from Laotian elephant cohort). The rabbit sera specific for gB peptides 1-5 used in this study (36,37), for 1 hour. After washing (three times with PBST), 100 µl/well TMB Substrate (Surmodics) was added, plates were incubated for 10 minutes in the dark, and the reaction was stopped by adding 100 µl 12,5% H2SO4.…”
Section: Expression Of Recombinant Eehv Proteinsmentioning
confidence: 99%